The implementation of integrated software for training and measuring creativity - Tan, Choon Keong (2008)
Every one of us has the potential to tap our own inner creative abilities and to make original and valued choices in our lives. The growing interest and concern in tapping creativity has prompted many researches on creativity to be undertaken in a number of countries, particularly Malaysia. This paper explored the use of Information and Communication Technology (ICT) as an important tool for fostering and assessing the creative potentials of a person. The researcher implemented an integrated system on 97 university undergraduates who would be potential teachers in the near future. Could computer be used to measure the creativity traits of a person? Could they improve their respective creative potentials? How did creativity improve? The research found that the assessment of creativity traits such as fluency, flexibility, elaboration and originality using computer was valid and possible using definitions and algorithms adapted from Torrance’s TTCT and Guilford’s Alternative Task (Torrance & Ball, 1984; Guilford, 1977). It was also found that 85 out of the 97 subjects managed to improve their respective fluency, flexibility, elaboration and originality scores in the posttest. The improvement of their creative potentials was pinpointed to the effective implementation of the Morphological Analysis Method in the brainstorming activities (pretest and posttest). The successful knowledge acquirement of the creativity technique by the subjects was due to the lively and effective delivery of multimedia training modules on the MA Method. It was recommended that the MA Method be adapted for repeated uses on any academic curriculums in schools or universities/colleges to improve the creative potentials of a person on long term basis.